Melancholy and "clásicos cotidianos". Towards a non-academy history of greek and latin literature in modern arts - García Jurado, Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
The hypothesis of a “non academic history of classical literature in modern authors” is proposed in this article. This kind of history against academic canon is not programmatic, but it simply appears, according to an hermeneutic method. Tensions such as “cosmopolitism versus localism, or “rare authors versus universal” articulate this history. Intertextual criteria -we call them “itineraries”- by which ancient literature appears in modern texts is perhaps the best way to present our history. These itineraries can be drawn according to the predominance of the ancient author (underlying texts), the text ín itself (quotations o appendix), commentaries (critical relations) o genres (several contacts among ancient and modern genres). Finally, we offer several instances of this history in great authors of the Twentieth Century.
Keywords: Canon; hermeneutics